THE EFFECT ON METACOGNITIVE STRATEGY OF STUDENTS' READING ABILITY OF DESCRIPTIVE TEXT - Nurul Aisyah; Destri Wahyuningsih; Widi Syeftinentias (Program Studi Pendidikan Bahasa Inggris, 2026)
Reading ability is an important skill in learning English, but many students still face difficulties in understanding descriptive texts. This study aimed to examine the effect of Metacognitive Strategy on students’ reading ability of descriptive text at the eleventh grade of SMKN 1 Kelayang. The research used a quantitative method with a true experimental design consisting of pre-test and post-test control groups. The sample consisted of an experimental class and a control class. Data were collected through reading tests and analyzed using SPSS. The findings showed that the experimental class achieved a higher post-test mean score (84.53) than the control class (76.82). The result of the independent sample t-test indicated that the significance value was lower than 0.05, which means that Metacognitive Strategy had a significant effect on students’ reading ability. In conclusion, Metacognitive Strategy is effective in improving students’ reading ability and encouraging active learning.